Lineages embedded in temple networks Daoism and local society in Ming China - Wang, Richard G. (Harvard University Asia Center, 2022)
"Lineages Embedded in Temple Networks explores how elite Daoists played a key role in the social and cultural life of local society in Ming China, notably by mediating between local networks-biological lineages, territorial communities, temples, and festivals-and the state. They did this through their organization in clerical lineages-their own empire-wide networks for channeling knowledge, patronage, and resources-and by controlling central temples that were nodes of local social structures. In this book, the only comprehensive social history of local Daoism during the Ming largely based on literary sources and fieldwork, Richard G. Wang delineates the interface between local organizations (such as lineages and temple networks) and central state institutions. While part 1 sets the framework for viewing Daoism as a social institution in regard to both its religious lineages and its service to the state in the bureaucratic apparatus to implement state orthodoxy, part 2 follows four cases to reveal the connections between clerical lineages and local networks. In the end, Wang illustrates how Daoism brought the cosmological order and universal salvation to local society, while at the same time granting divine sanction and political legitimacy to the state"--
Keywords: Gesellschaft; Mingdynastie; Taoismus; China; Taoism / Social aspects / China / History; Taoist temples / China / History; Taoism and state / China / History; Taoists / China / History; Social networks / China / History; China / History / Ming dynasty, 1368-1644; China / Civilization / Taoist influences; RELIGION / General; Civilization / Taoist influences; Social networks; Taoism and state; Taoism / Social aspects; Taoist temples; Taoists; 1368-1644; History